2015
DOI: 10.1177/0148607115577817
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Is Superior to Citrate in Oral Rehydration Solution in the Protection of Intestine via Hypoxia‐Inducible Factor‐1 Activation in Rats With Burn Injury

Abstract: Pyr-ORS provides a superior option to Cit-ORS for the preservation of intestinal blood flow and barrier function and the attenuation of histopathological alterations in enteral resuscitation of rats with burn injury. Its underlying mechanism may be closely related to the pyruvate in activation of intestinal HIF-1-EPO signaling cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Moreover, erythropoietin (EPO), a typical up-regulative gene induced by HIF-1α, has cyto-protective and anti-inflammatory functions under various pathological conditions [ 68 , 69 ]. It was demonstrated that pyruvate-enriched ORS (Pyr-ORS) significantly preserved the intestinal function and markedly elevated intestinal EPO in the enteral resuscitation of rats with burn injury compared with the effects of citrate-enriched ORS (Cit-ORS) [ 70 ]. Therefore, pyruvate may promote the correction of LA via its activation of the HIF-1α-EPO signaling pathway and improvement of cell metabolism.…”
Section: Pyruvate As a Potential Candidate For La Correctionmentioning
confidence: 99%
“…Moreover, erythropoietin (EPO), a typical up-regulative gene induced by HIF-1α, has cyto-protective and anti-inflammatory functions under various pathological conditions [ 68 , 69 ]. It was demonstrated that pyruvate-enriched ORS (Pyr-ORS) significantly preserved the intestinal function and markedly elevated intestinal EPO in the enteral resuscitation of rats with burn injury compared with the effects of citrate-enriched ORS (Cit-ORS) [ 70 ]. Therefore, pyruvate may promote the correction of LA via its activation of the HIF-1α-EPO signaling pathway and improvement of cell metabolism.…”
Section: Pyruvate As a Potential Candidate For La Correctionmentioning
confidence: 99%
“…The signals were inputted into the computer to plot curves; data were expressed as blood perfusion units (PBU), as previously described. 14 Animal grouping, ORS preparation, and rehydration Randomly, 80 rats were divided into four groups (N ¼ 20, two subgroups at 8 h and 24 h in each group: n ¼ 10): the scald group with no fluid resuscitation (group NR); scald resuscitation group with low-osmolar Cit-ORS (WHO-ORS III, group CR); scald resuscitation group with low-osmolar Pyr-ORS (group PR), and scald sham group (group SR). Following the WHO-ORS formula, the reduced osmolarity of Pyr-ORS or Cit-ORS was made with 3.5 g sodium pyruvate or 2.9 g tri-sodium citrate dihydrate (SigmaeAldrich), 2.0 g or 2.5 g NaCl, and 1.5 g KCl plus 13.5 g anhydrous glucose in distilled water up to 1000 mL at the laboratory.…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
“…30,31 Furthermore, gluconeogenesis may be favorably preserved via the stimulation of hypoxia-inducible factor-1a as a consequence of prolyl hydroxylase inhibition by pyruvate, relative to citrate. 14,31,32 Besides, improved organ function, particularly heart, liver, and kidney, by pyruvate facilitates tissue oxygenation and lactate clearance.…”
Section: Major Findingsmentioning
confidence: 99%
“…; Helix Medical, Inc., Carpinteria, CA, USA) in the vena cava through the right external jugular vein for PN. The catheter was tunneled subcutaneously and exited at the midpoint of the tail [26]. Then a 3-cm incision was made in the skin just below the sternum, and a silicon rubber tube (medical grade, 0.020 i.d.…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min, the clip was removed and the abdominal incision was closed. Rats were separately housed in metal cages with wire grid floors to eliminate coprophagia, and partially immobilized by tail restraint to protect the catheter during infusion [26,28]. This technique of infusion in the rat has been adopted in several studies to keep the animals from hyperactivity, which may break the tubes.…”
Section: Methodsmentioning
confidence: 99%